Integrated Social Cognitive and Social Capital Theory Toward Telemedicine Acceptance During Pandemic Turbulence - Darmasetiawan, Noviaty Kresna; Rianawati, Andri; Prakoeswa, Flora Ramona Sigit (Program MM Universitas Surabaya, 2024)
Pupose: This paper investigates the acceptance of telemedicine during the COVID-19 pandemic using an integrated framework of social cognitive theory, social capital, and the Technology Acceptance Model (TAM). Method: The research employs a quantitative method through online surveys. The findings indicate that: 1) Self-efficacy is associated with the perception of ease of use of telemedicine. 2) Social capital is related to both the perceived ease of use and usefulness of telemedicine. 3) The turbulent pandemic situation strengthens the intention to use telemedicine. This study collect 155 respondents and use partial least square for testing hypothesis. Result: All of hypothesis in this research are supported. The results suggests that the implementation of telemedicine should consider social capital, social cognitive aspects, and TAM.